2011
DOI: 10.5812/aapm.3443
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management After Surgery: A Brief Review

Abstract: Postoperative pain management is an important but undervalued aspect of perioperative care, we have emphasized the importance of postoperative analgesia and discussed the new developments in this field. This article is recommended to be read by all anesthesiologists, neurosurgeons and any other physicians who involved with pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Pain control is a multi-modal approach (6, 7, 22), so all the studies and all pharmacologic interventions try to find better ways to for pain control. Our study had some limitations, but generally showed that attenuation of post-operative pain through magnesium added to opioids suggests a new pharmacologic therapy to control better post-operative pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain control is a multi-modal approach (6, 7, 22), so all the studies and all pharmacologic interventions try to find better ways to for pain control. Our study had some limitations, but generally showed that attenuation of post-operative pain through magnesium added to opioids suggests a new pharmacologic therapy to control better post-operative pain.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the extensive use of magnesium sulphate in obstetric practice makes the anesthesiologists familiar with the pharmacological action of this drug and its interaction with anesthetic agents. Third, it’s some properties may be valuable in certain areas of anesthetic practice (5-7). As mentioned above, we need to use some methods or drugs to decrease the dosage of opioid (opioid sparing effect).…”
Section: Introductionmentioning
confidence: 99%
“…Cesarean section constitutes a public health priority (1, 11) because it is one of the main surgeries in the obstetrics and gynecologist wards and its rate is increasing due to increased marital age, legal issues in obstetric/gynecologic ward, and socio-economic status of the community, and prevention of its postoperative complications is of great importance (2). One of the main postoperative complications of cesarean is pain (3).…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pain affects the patients’ operative outcome (11) and since 1990, the effect of magnesium on postoperative pain and its effect on postoperative opioid consumption, has been studied on gynecologic surgery, ophthalmic surgery, arthroscopic, and lumbar interventions.…”
Section: Introductionmentioning
confidence: 99%